Kalanchoe ×edwardii (Crassulaceae subfam. Kalanchooideae), a nothospecies derived from K. beharensis and K. tomentosa - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2020)
The recently described Kalanchoe ×gildenhuysii Smith & Figueiredo (2020: 43) and K. ×hummeliae Smith (2020a: 91) both have K. millotii Hamet & Perrier de la Bâthie (1912: 374) as one parent, with the other parent being K. tomentosa Baker (1882: 110) and K. beharensis Drake del Castillo (1903: 41), respectively. These three species are shrubby or arborescent; virtually throughout densely tomentose, although to a much lesser extent on the adaxial surfaces of the petal lobes; have prominent calyces that in some cases obscure much of the corolla tube; and rather dull coloured flowers, except in K. tomentosa that can have strongly purple-infused to purple corollas. These species of Kalanchoe Adanson (1763: 248) all originate from Madagascar, a present-day and likely historic centre of high species diversity for the genus (Gehrig et al. 2001, Descoings 2003, Smith & Figueiredo 2018).